KETERSEDIAAN PAKAN GAJAH SUMATERA (Elephas maximus sumatranus Temminck, 1847) DI RESORT AIR HITAM TAMAN NASIONAL TESSO NILO KABUPATEN PELALAWAN PROVINSI RIAU - Edi, Eko; Erianto, .; Erianto, .; Prayogo, Hari; Prayogo, Hari (Universitas Tanjungpura, 2017)
The tesso nilo national park (TNNP) is a nature conservation area located in Pelalawan Regency, Riau Province with an area of Â±83,068 hectares. The TNNP is administratively located in two districts of Pelalawan and Indragiri Hulu in Riau Province. This region has the type of lowland tropical rain forest, with a height of 50-175 m above sea level with flat to hilly topography. This research aims to identify the food source availability for sumatran elephants ( Elephas maximus sumatranus). This research was conducted at the Air Hitam Resort In Tesso Nilo National Park, Pelalawan Regency of Riau Province which was held from 27 April to June 20, 2016. The locations of the study were divided into three habitat types, namely: open habitat and swamps, shrub and natural forest. The amount of food for elephants found at the Air Hitam Resort TNNP is composed of 39 species of the open habitat and 7 species of the swamp, shrub habitat 9 species and 22 species of natural forest habitat. The overall support capacity of elephant food at the Air Hitam Resort TNNP with an area of 11,252 ha is 39,472.61 individuals/day and can accommodate as many as 798 elephants. The number of elephants found in the research sites was as many as 25-30 individuals (seen from the groups of elephants spread across the research sites). Keywords: feed, sumatran elephants, Tesso Nilo National Park.